AUTOMATISASI PENDAFTARAN RAWAT JALAN UNTUK MENINGKATKAN EFEKTIVITAS LAYANAN KESEHATAN DI KLINIK GIGI DRG. MIRANTI P DARMAWATI - Ivo Ayu Yuliani; Yuyun Yunengsih; Falaah Abdussalaam (POLITEKNIK PIKSI GANESHA, 2025)
The patient registration process at Klinik Gigi drg. Miranti P. Darmawati is still carried out manually, often causing long queues, data entry errors, and service delays. This study aims to develop an automated outpatient registration system to improve service effectiveness. The research applies the Waterfall method, starting from needs analysis, system design, implementation, and testing. Data were collected through observations of the registration process and interviews with clinic staff. The results show that the automation system can speed up the registration process, reduce data entry errors, and increase satisfaction for both patients and staff. It is recommended that the system be further developed with integration to electronic medical records and a schedule reminder feature to achieve more optimal healthcare services.